QBO Changes in CMIP6 Climate Projections. Issue 7 (8th April 2020) - Butchart, Neal; Anstey, James A.; Kawatani, Yoshio; Osprey, Scott M.; Richter, Jadwiga H.; Wu, Tongwen
Abstract: Phase 6 of the Coupled‐Model Intercomparison Project (CMIP6) is the first in which a significant number of models include a well‐resolved stratosphere. Changes in equatorial stratospheric variability in historical and Shared Socioeconomic Pathways (SSPs) scenario simulations are investigated in 10 models with realistic quasi‐biennial oscillations (QBO). All project a weakening of the QBO throughout the stratosphere for SSP370 and SSP585 scenarios and for 1960 to 2010. The weakening is strongest in the lower stratosphere, ranging from 5 . 8 ± 0 . 5 % to 4 . 3 ± 0 . 5 % to 2 . 0 ± 0 . 5 % per decade at 50 hPa for SSP585, SSP370, and historical simulations, respectively. At 20 hPa a weakening of both westward and eastward phases contributes though the weakening eastward phase is only seen in 7 of the 10 models. Similar robust weakening occurs for the temperature QBO, but only from 30 hPa upward. In both scenarios the QBO period decreases in 7 of the 10 models. Plain Language Summary: At altitudes between roughly 16 and 50 km the equatorial atmosphere is dominated by strong zonal winds that reverse sign from eastward to westward roughly every 14 months in what is referred to as the quasi‐biennial oscillation. With developments in models the quasi‐biennial oscillation now features in a significant number of the latest state‐of‐the‐art climate projections. In those projections featuring the oscillation, the changing climate weakens it by up to ∼ 6% per decade for the more extreme of the scenarios considered. Somewhat less certain is a shortening of the time between wind reversals in several of the projections. Key Points: Many more CMIP6 models simulate a QBO than in previous CMIP phases A weakening of the QBO in response to climate change is projected by 10 CMIP6 models with realistic QBOs Under warming scenarios QBO periods shorten in 7 of the 10 CMIP6 models with realistic QBOs